Effects of Climate Change, Land Use and Land Cover Variability on Green and Blue Water in Wami/Ruvu Basin, Tanzania - Lazaro, Benson HM; Hagai, Martine M; Mato, Rubhera RAM (Tanzania Journal of Science, 2023)
Water basins are the primary food sources, giving green water and blue water worldwide. Despite the basins’ potential, information on the periodical variations in blue water and green water is sparse, particularly in developing countries. The study specifically evaluated the changes in land use and land cover variability (LULCV), effects of land use and land cover variability on green water and blue water variations, and effects of climatic changes on green water and blue water. The evaluation involved the Enhanced Thematic Mapper and Operational Land Imager satellite images of 1990, 2000, 2010 and 2020. Image processing utilized the Soil and Water Assessment Tool (SWAT) in ArcGIS software. The land use and land cover variabilities indicated that land use supporting social-economic activities increased, while natural land cover decreased. Proportionally, blue water per annum was decreasing due to declining natural vegetation, enhanced by the increased socio-economic activities. Whereas, the increase in green water per annum was due to the increased temperatures, boosted by climate changes. Since the temperature rise is mainly uncontrolled, greenhouse farming should be encouraged for making green water more productive in agriculture and communities should be encouraged to practice environmentally friendly anthropogenic activities for sustainable green water and blue water management. Keywords: Basin, Green water, Blue water, SWAT model, Climate change